Outcomes of ⩽6-month versus 12-month dual antiplatelet therapy after drug-eluting stent implantation: A meta-analysis and meta-regression. Issue 52 (December 2016) - Villablanca, Pedro A.; Massera, Daniele; Mathew, Verghese; Bangalore, Sripal; Christia, Panagiota; Perez, Irving; Wan, Ningxin; Schulz-Schüpke, Stefanie; Briceno, David F.; Bortnick, Anna E.; Garcia, Mario J.; Lucariello, Richard; et al.
Abstract: Background: The benefit of ⩽6-month compared with 12-month dual antiplatelet therapy (DAPT) after percutaneous coronary intervention (PCI) with drug-eluting stent (DES) placement remains controversial. We performed a meta-analysis and meta-regression of ⩽6-month versus 12-month DAPT in patients undergoing PCI with DES placement. Methods: We conducted electronic database searches of randomized controlled trials (RCTs) comparing DAPT durations after DES placement. For studies with longer follow-up, outcomes at 12 months were identified. Odds ratios and 95% confidence intervals were computed with the Mantel–Haenszel method. Fixed-effect models were used; if heterogeneity ( I 2 ) > 40 was identified, effects were obtained with random models. Results: Nine RCTs were included with total n = 19, 224 patients. No significant differences were observed between ⩽6-month compared with 12-month DAPT in all-cause mortality (OR 0.87; 95% confidence interval (CI): 0.69–1.11), cardiovascular (CV) mortality (OR 0.89; 95% CI: 0.66–1.21), non-CV mortality (OR 0.85; 95% 0.58–1.24), myocardial infarction (OR 1.10; 95% CI: 0.89–1.37), stroke (OR 0.97; 95% CI: 0.67–1.42), stent thrombosis (ST) (OR 1.37; 95% CI: 0.89–2.10), and target vessel revascularization (OR 0.95; 95% CI: 0.77–1.18). No significant difference in major bleeding (OR 0.72; 95% CI: 0.49–1.05) was observed, though the all-bleeding event rate was significantly lower in the ⩽6-month DAPT group (OR 0.76; 95% CI: 0.59–0.96). In the meta-regression analysis, a significant association between bleeding events and non-CV mortality with 12-month DAPT was found, as well as between ST and mortality in addition to MI with ⩽6-month DAPT. Conclusion: DAPT for ⩽6 months is associated with similar mortality and ischemic outcomes but less bleeding events compared with 12-month DAPT after PCI with DES. Abstract : Supplemental Digital Content is available in the text